The first case of periorbital human dirofilariasis in the Czech Republic - Gebauer, Jan; Ondruš, Jaroslav; Kulich, Pavel; Novotný, Ladislav; Sałamatin, Rusłan; Husa, Petr; Novobilský, Adam (Parasitology research, 2021)
Dirofilaria repens and Dirofilaria immitis are the most common filarial species affecting humans in Europe. Dirofilaria repens causes subcutaneous or ocular infection, whereas D. immitis is responsible mainly for the pulmonary form. In this report, we present the first human case of periorbital dirofilariasis in the Czech Republic. A 58-year-old woman suffered from an eyelid oedema, redness and pain in the left eye. After excising the parasite from her eyelid, all clinical symptoms disappeared. Based on the morphology and cytochrome oxidase I sequencing, the parasite was identified as D. repens. Histology revealed that the excised worm was female with absent microfilariae in uteri. With respect to the length of the incubation period and the sequence identity with a known Czech isolate, we concluded that D. repens was most likely of autochthonous origin.
Keywords: Filarial; Microfilariae; Human; oční infekce parazitární; Eye Infections, Parasitic; Dirofilaria repens; Dirofilariasis; Česká republika; proteiny červů; Middle Aged; mikrofilárie; Microfilaria; Czech Republic; Cyclooxygenase 1; Ocular infection; Helminth Proteins; ženské pohlaví; zvířata; Humans; Cytochrome oxidase I; Eye; lidé středního věku; cyklooxygenasa 1; Clinical symptom; Female; dirofilarióza; lidé; Animals